Tracheal Resection and Anastomosis for Postintubation Tracheal Stenosis: A Case Report - Acharya, Anup; Singh, Madan Mohan; Tambay, Yeshwant Gajanan (Journal of Lumbini Medical College, 2016)
Introduction: Tracheal stenosis is one of the dreaded complication of tracheal intubation. Tracheal resection and anastomosis is an established definitive treatment for stenosis more than one cm. Here, we present a case of post-intubation tracheal stenosis managed by resection and anastomosis, first of its kind in our centre. Case Report: We present a case of 26-year female who underwent tracheal intubation during her treatment of tubercular meningitis. Two weeks later, she returned with respiratory difficulty. A diagnosis of post-intubation tracheal stenosis was made. Tracheal resection and anastomosis was done. Recovery was uneventful and she was discharged on 14th post-operative day. Conclusion: Post-intubation tracheal stenosis is still a dreaded complication even after the introduction of high volume low pressure cuff. They can be successfully managed. Care personnel in intensive care unit (ICU) should perform to prevent this complication. Journal of Lumbini Medical College. 2014;2(2):48-50.